Relationship between Hemodialysis Frequency and Urea Reduction Ratio (URR) Results in CKD Patients - Nuniek Setyo Wardani; Nyoto Heriyanto; Moch Robby Fajar Cahya; Sondang Manurung; Intan Parulian (GLOBAL HEALTH SCIENCE GROUP, 2025)
Chronic Kidney Disease (CKD) is an irreversible condition characterized by structural and functional abnormalities of the kidneys. Patients in the early stages of CKD usually do not experience any complaints until a decline in kidney function necessitates hemodialysis. Patients undergoing hemodialysis gradually experience a reduction in urea levels. Daily dietary habits and patient compliance play a crucial role in regulating urea levels. The aim of this study is to determine the relationship between the frequency of hemodialysis and the URR (Urea Reduction Ratio) results in CKD patients at RSUD Tarakan.This research was carried out from August 2024 to January 2025. It is a descriptive correlational study employing a cross-sectional approach with total sampling, involving 93 respondents. The results showed that the majority of respondents (82.8%) regularly underwent hemodialysis twice a week, and their average URR increased by 79.6%. Cross-tabulation analysis yielded a p-value of 0.026 (< 0.05), indicating a significant relationship between hemodialysis frequency and URR values in patients at RSUD Tarakan. The strength of the association was determined to be r = 0.231, implying a low/weak correlation between the hemodialysis frequency and URR values.It is recommended that the hospital provide educational sessions or seminars on the importance of hemodialysis to enhance patient motivation for undergoing the procedure.